A novel isoquinoline mitophagy inducer ameliorates paclitaxel-induced peripheral neuropathy in Drosophila and mouse models - Sangwoo Im; Se Myeong Choi; Young Yeon Kim; Dae Jin Jeong; Jee-Hyun Um; Kang-Min Lee; Eunhee Yoo; Jong Hyun Cho; Ji Hyun Lee; Jeanho Yun (Scientific Reports)
Abstract Chemotherapy-induced peripheral neuropathy (CIPN) resulting from neurodegeneration due to chemotherapy is a challenging complication of widely administered anticancer drugs including paclitaxel. Although CIPN is common and limits the use of chemotherapies, no curative treatment for CIPN has been developed. Recently, stimulation of mitophagy has emerged as a promising strategy for treating neurodegenerative diseases, but studies on its therapeutic effects on CIPN are limited. In this study, we examined the therapeutic effect of the recently developed mitophagy inducer ALT001 on paclitaxel-induced peripheral neuropathy model in Drosophila and mice. Importantly, ALT001 administration in a paclitaxel-induced Drosophila model of peripheral neuropathy significantly ameliorated paclitaxel-induced alterations in sensory neurons and the thermal hyperalgesia phenotype in a mitophagy-dependent manner. Moreover, we demonstrated that ALT001 administration significantly ameliorated paclitaxel-induced mechanical allodynia and the reduction in intraepidermal nerve fiber density in a mouse model. Interestingly, ALT001 did not interfere with the cytotoxic effect of paclitaxel on lung cancer or breast cancer cells. Our results suggest that ALT001 is a potential candidate for the treatment of paclitaxel-induced peripheral neuropathy and that stimulation of mitophagy is a promising strategy for CIPN treatment that does not affect the cytotoxic effect of chemotherapy.